Litter accumulation and fire risks show direct and indirect climate-dependence at continental scale - Mark A. Adams; Mathias Neumann (Nature Communications)
Abstract Litter decomposition / accumulation are rate limiting steps in soil formation, carbon sequestration, nutrient cycling and fire risk in temperate forests, highlighting the importance of robust predictive models at all geographic scales. Using a data set for the Australian continent, we show that among a range of models, most of the variance in litter mass over a 40-year time span can be accounted for by a parsimonious model with elapsed time, and indices of climate and litter quality, as independent drivers. Climate is an important driver of variation in both the species identity of dominant eucalypts and litter accumulation across the continent. Litter quality shows emergent properties of climate-dependence and contributes to explained variance. Nonetheless, elapsed time dominated explained variance in litter mass (up to 90%) at continental scale. Results provide guidance for future decomposition studies. Algorithms reported here can significantly improve accuracy and reliability of predictions of carbon and nutrient dynamics and fire risk.